GAMIFICATION IN TEACHING ENGLISH: HOW GAMES CAN BOOST LEARNING (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
In recent years, gamification has emerged as a significant trend in education, bringing the engaging and motivating elements of games into learning environments. By integrating game mechanics—such as point scoring, competition, and rewards—into traditional education, gamification aims to make learning more enjoyable and effective. This article will explore how gamification enhances English teaching by fostering motivation, increasing retention, providing immediate feedback, and encouraging collaboration. It will also examine various tools and techniques that teachers can incorporate into their classrooms.